Limonin induces ferroptosis in cervical squamous cell carcinoma by activating the expression of soluble epoxide hydrolase 2 protein - Qi Wu; Suning Bai; Pei Wang; Lina Han; Liyun Song; Luyang Su; Yanan Ren (PLoS ONE, 2026)
Natural products are a rich sources for developing anti-cancer drugs with low toxicity and high efficiency. Limonin has anti-cancer activity; however, its effect on cervical squamous cell carcinoma remains unreported. The aim of this study was to explore how Limonin affects ferroptosis in cervical squamous cell carcinoma (CESC) and its underlying mechanism. Based on differential gene analysis of the Gene Expression Omnibus database and drug target prediction of the Comparative Toxicogenomics Database, combined with molecular docking technology, potential anti-cancer targets of Limonin were identified. In vitro experiments were conducted to create epoxide hydrolase 2 ( EPHX2) knockdown and overexpression cell lines. Relevant phenotypic experiments were conducted to verify how Limonin targeting EPHX2 affects cell proliferation and ferroptosis. Integrated bioinformatic analysis revealed EPHX2 as a key target of Limonin. Functional experiments showed that EPHX2 overexpression inhibited the proliferation of CESC and induced ferroptosis, while Limonin treatment could enhance EPHX2 expression in a concentration-dependent manner. Furthermore, EPHX2 knockdown could reverse the inhibitory effect of Limonin on CESC proliferation and alterations in ferroptosis-related indicators. This study results reveals a new mechanism by which Limonin induces ferroptosis in CESC by activating EPHX2, providing a new strategy for natural compound-based ferroptosis-targeted therapy.